Analisis Peran Petugas Apron Movement Control (AMC) Dalam Peningkatan Keselamatan Penerbangan Di Area Apron Bandara Udara Internasional Jenderal Ahmad Yani Semarang - Tutut Dwi Meilani; Febriansyah Ignas Pradana (Jurnal Publikasi Ilmu Manajemen, 2023)
The higher the number of people or users of air transportation services, the more human resources are needed as service providers to ensure the safety and security of passengers. An airport must pay attention to safety, security and flight control on the air side carried out by the Apron Movement Control (AMC) unit. An oil spill in the apron area of General Ahmad Yani International Airport, Semarang, can be fatal because it can disrupt flight safety. This study aims to determine the role of Apron Movement Control (AMC) officers in improving flight safety in the apron area and to find out whether this role has been able to improve safety in the Semarang Airport apron area or not. This research is qualitative by using data collection methods in the form of observation, interviews, and documentation. The data obtained are primary and secondary. This research was conducted in September 2023. From this research it can be seen that the role of Semarang Airport AMC officers is to improve safety in the apron area. Provide outreach to all personnel to look after each other and remind if something creates a hazard, Maintain and coordinate to keep the Apron clean. And Manage parking stands to reduce hazard when in peak hours. The role of the Semarang Airport AMC Unit has been able to improve safety because there is action of each duty and obligation. This role has been able to improve flight safety in the Apron Area of General Ahmad Yani International Airport Semarang, namely the role of the AMC Unit has been able to increase safety on the air side because each AMC officer has fulfilled the competence of each officer, and they carry out their duties properly according to the rules set.